How Does AI Analyze Pathology Slides for Cancer Diagnosis? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Pathology, the microscopic examination of tissue samples, is the cornerstone of cancer diagnosis. Pathologists analyze tissue slides to identify malignant ce...
Keywords: AI in Medical Imaging and Diagnostics; Analyze; Pathology; Slides; Artificial Intelligence; Machine Learning; Deep Learning